Serologic and genetic characterization of Plasmodium vivax from whole blood-impregnated filter paper discs. - Kain, Kevin C.; Wirtz, Robert A.; Fernández Salas, Ildefonso; Franke, Eileen D.; Rodríguez, Mario Henry; Lanar, David (The American journal of tropical medicine and hygiene., 1992)
The presence in the New World of a variant strain of Plasmodium vivax (VK247) containing a unique circumsporozoite (CS) repeat domain was determined by the detection of antibodies to the variant CS protein and by genetic analysis of the CS gene from field isolates. Whole blood specimens were collected on filter paper from patients infected with P. vivax in Mexico and Peru. Plasmodium vivax DNA was eluted from filter paper samples and the CS gene was amplified by the polymerase chain reaction (PCR) and analyzed for the presence of VK247 or VK210 DNA by oligoprobe hybridization. Sera eluted from a companion filter paper sample were screened for antibodies reactive with the predominant and variant repeat peptides by enzyme-linked immunosorbent assays (ELISA) and with sporozoites by the immunofluorescent antibody (IFA) test. All 24 patients were positive by PCR and oligoprobe hybridization for either VK210 (16 of 24), VK247 (3 of 24), or both (5 of 24). Mixed infections were common (5 of 7) in Peru, but were not observed in the Mexican isolates (0 of 17). All three VK247 infections from Mexico occurred in residents of the foothills above Tapachula (P = 0.02). Of patients with smear-positive P. vivax infection, 42% (10 of 24) had detectable antibodies eluted from dried blood dots that were reactive with the CS protein by IFA or ELISA. These findings establish the widespread distribution of the P. vivax variant CS protein in the New World and indicate that dried blood filter paper samples represent a valuable source of material for the serologic and molecular analysis of plasmodial infections.